1999
DOI: 10.1152/ajpheart.1999.277.1.h128
|View full text |Cite
|
Sign up to set email alerts
|

Delayed preconditioning with adenosine is mediated by opening of ATP-sensitive K+ channels in rabbit heart

Abstract: The adenosine agonist 2-chloro- N 6-cyclopentyladenosine (CCPA) induces delayed ischemic protection in vivo. We hypothesized that this protection is mediated by opening of ATP-sensitive K+(KATP) channels and increased synthesis of 72-kDa heat shock protein (HSP 72). Six groups ( n = 9–13 animals/group) of animals were studied: group I, control rabbits that received no treatment; group II, animals given glibenclamide (0.3 mg/kg iv) 30 min before ischemia; group III, animals given 5-hydroxydecanoate (5-HD; 5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
1
38
2
Order By: Relevance
“…For example, we 51 and others 52 have demonstrated that A 1 R-induced delayed preconditioning is dependent on the opening of the ATP-sensitive K ϩ (K ATP ) channels during the index ischemic insult, because inhibition of K ATP channels with glibenclamide or 5-hydroxydecanoate abrogated the infarct-limiting effect of treatment with CCPA 24 hours earlier. Furthermore, on the basis of the relative selectivity of 5-hydroxydecanoate for the mitochondrial rather than the sarcolemmal K ATP channels, it has been proposed that opening of the former may mediate the delayed cardioprotective effects of A 1 R agonists.…”
Section: Other Mediators Of a 1 R-induced Delayed Preconditioningmentioning
confidence: 96%
“…For example, we 51 and others 52 have demonstrated that A 1 R-induced delayed preconditioning is dependent on the opening of the ATP-sensitive K ϩ (K ATP ) channels during the index ischemic insult, because inhibition of K ATP channels with glibenclamide or 5-hydroxydecanoate abrogated the infarct-limiting effect of treatment with CCPA 24 hours earlier. Furthermore, on the basis of the relative selectivity of 5-hydroxydecanoate for the mitochondrial rather than the sarcolemmal K ATP channels, it has been proposed that opening of the former may mediate the delayed cardioprotective effects of A 1 R agonists.…”
Section: Other Mediators Of a 1 R-induced Delayed Preconditioningmentioning
confidence: 96%
“…Previous studies have shown that A 1 AR activation induces delayed protection in the rabbit heart. 4,6 This protection was attributed to the activation of protein kinase C (PKC) 10 and opening of the K ATP channel. 6,11 In the present study, we have shown a novel mechanism of A 1 AR-induced delayed cardioprotection in the isolated perfused mouse heart.…”
Section: Salient Findingsmentioning
confidence: 99%
“…4,6 This protection was attributed to the activation of protein kinase C (PKC) 10 and opening of the K ATP channel. 6,11 In the present study, we have shown a novel mechanism of A 1 AR-induced delayed cardioprotection in the isolated perfused mouse heart. Stimulation of A 1 ARs with CCPA resulted in delayed cardioprotection, as indicated by a significant reduction in infarct size and improvement in postischemic ventricular function.…”
Section: Salient Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have identified the opening of K ATP -channels as an endeffector, mediating the infarct-sparing effects of late IP (84)(85)(86)(87)(88). The opening of these channels was associated with the infarct-sparing effect of late IP but not found necessary for the protection against stunning (89).…”
Section: Late Ipmentioning
confidence: 99%